2005
DOI: 10.1155/2005/512012
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of a new dihalocyclopropane‐dihalomethyl vinyl rearrangement

Abstract: A tentative mechanism for a new dihalocyclopropane-dihalomethyl vinyl rearrangement is discussed following some isotopic labelling and substituted cyclohexene studies on fused cyclohexene-cyclopropane (norcarane) compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In our last study [2], we discussed the three most plausible mechanistic pathways and concluded that, under Hiyama conditions, the overall results tend to indicate the absence of the ionic intermediates.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…In our last study [2], we discussed the three most plausible mechanistic pathways and concluded that, under Hiyama conditions, the overall results tend to indicate the absence of the ionic intermediates.…”
Section: Dear Editormentioning
confidence: 99%
“…In our previous two papers, we have shown that this rearrangement proceeds via a unique pathway of a Hiyama-like system, where the presence of two neighbouring oxidation state metal cations is necessary [1,2]. This reaction did not follow the Makosza pathway of ring extension, which would lead, in the case of for example bicyclic compounds such as cis-fused 7,7-dichlorocarenes (1) (with gem-dichlorocyclopropane ring condensed on the cyclohexane frame), to halogenated cycloheptene (3) compounds [3,4].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…86,87 Here, the reaction proceeds via a biradical mechanism involving Cr intermediate and the mechanistic study was performed by isotopic labeling. 86,87 Here, the reaction proceeds via a biradical mechanism involving Cr intermediate and the mechanistic study was performed by isotopic labeling.…”
Section: Rearrangementsmentioning
confidence: 99%
“…A detailed mechanistic study of the rearrangement of both exocyclic and endocyclic dihalocyclopropane to cyclohexene was also reported. 86,87 Here, the reaction proceeds via a biradical mechanism involving Cr intermediate and the mechanistic study was performed by isotopic labeling. Under acidic conditions in the presence of Cr 2+ /Cr 3+ , dihalocyclopropanes generate a dihalomethyl vinyl derivative; the existence of the latter was presumed since a mixture of α,β-unsaturated aldehyde and acid along with dehalogenated products were isolated from the reaction mixture (Scheme 55).…”
Section: Rearrangementsmentioning
confidence: 99%